Habitat Selection and Population Density of Diurnal and Nocturnal Lemurs in the Anjozorobe-Angavo Protected Area, Madagascar - Giulia Sassoli; Aurelia Sebastiani; Davide Mirante; Hanitriniaina Raharinirina; Rojotiana N. Rakotoarisoa; N. M. Koloina Rakotoarivelo; Fanomezantsoa L. Ravololoniaina; H. Domohina S. Randrianarisoa; Gabriele Ferraro; S. Jacques Rakotondranary; Timothy M. Eppley; Luca Santini (International Journal of Primatology, 2026)
Primates are among the most threatened mammals globally owing to rapid habitat loss and intense hunting pressure. Among these, lemurs are the taxon with the highest number of species at risk of extinction. Although many lemur species have been surveyed extensively across Madagascar, some taxa and protected areas remain understudied. The Anjozorobe-Angavo Protected Area, a rainforest landscape in the highlands of central-eastern Madagascar, has received relatively little ecological attention and continues to experience deforestation. This study was designed to estimate the population density and habitat selection of diurnal and nocturnal lemur species within La Mananara, a privately owned forest within Anjozorobe-Angavo. We conducted line-transect surveys over a 3-month period, between October and December 2024, and applied distance sampling to estimate species abundance. We also collected data on species detection locations and established vegetation plots to characterize habitat structure and evaluate species-specific habitat associations through resource selection functions. We recorded four diurnal and six nocturnal lemur species. Nocturnal species exhibited higher estimated densities and were more frequently encountered in areas with human activity, whereas diurnal species were less abundant and generally showed stronger associations with areas characterized by greater canopy cover and lower anthropogenic disturbance. Our findings underscore the conservation importance of primary forest protection, while also demonstrating the role of edge habitat and human-modified habitats for certain nocturnal taxa. These density estimates represent a quantitative assessment for this area, helping to inform the management of La Mananara, and contributing to broader conservation assessments of lemur populations within this under-characterized protected landscape.

Monte San Nicola (Sicily): Gelasian GSSP and base Quaternary/Pleistocene - L. Capraro; S. Bonomo; A. Incarbona; F.J. Hilgen; E. Zanola; A. Di Stefano; F. Dela Pierre; S. Ferraro; P. Ferretti; E. Fornaciari; S. Galeotti; P. Macrì; et al. (Quaternary Science Reviews, 2026)

Detection of Dengue virus RNA in Wastewater during a Local Epidemic in Central Italy (August–October 2024) - P. Mancini; C. Veneri; G. Bonanno Ferraro; A. Franco; M. Iaconelli; D. Brandtner; L. Lucentini; G. Venturi; E. Mancuso; G. Marsili; M. Del Manso; C. Sacco; et al. (Food and Environmental Virology, 2025)

Climate change and occupational health and safety. Risk of injuries, productivity loss and the co-benefits perspective - A. Marinaccio; C. Gariazzo; L. Taiano; M. Bonafede; D. Martini; S. D'Amario; F. de’Donato; M. Morabito; Filippo Ariani; Alessandra Binazzi; Andrea Bogi; Michela Bonafede; et al. (Environmental Research, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Exploring the underwater life in transitional environments: Benthic foraminifera, ostracods, and dinoflagellate cysts – Biotic trends and EcoQS assessment in the Mar Piccolo of Taranto (Ionian sea, southern Italy) - F. Francescangeli; L. Ferraro; F. Frontalini; S. Da Prato; F. Rubino (Marine Environmental Research, 2024)

Diagnostic value of two-dimensional echocardiographic measurements of the pulmonary artery diameter and the pulmonary artery distensibility index to detect pulmonary hypertension in horses - A. Ferraro; S. Hartnack; C.C. Schwarzwald (Journal of Veterinary Cardiology, 2023)

A State-of-the-Art Scoping Review on SARS-CoV-2 in Sewage Focusing on the Potential of Wastewater Surveillance for the Monitoring of the COVID-19 Pandemic - G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; E. Suffredini; L. Bonadonna; L. Lucentini; A. Bowo-Ngandji; C. Kengne-Nde; D. S. Mbaga; G. Mahamat; H. R. Tazokong; et al. (Food and Environmental Virology, 2022)

Hepatitis E Virus in Water Environments: A Systematic Review and Meta-analysis - G. R. Takuissu; S. Kenmoe; L. Ndip; J. T. Ebogo-Belobo; C. Kengne-Ndé; D. S. Mbaga; A. Bowo-Ngandji; M. G. Oyono; R. Kenfack-Momo; S. Tchatchouang; J. Kenfack-Zanguim; R. Lontuo Fogang; et al. (Food and Environmental Virology, 2022)
Hepatitis E virus (HEV) is responsible for acute hepatitis in humans, through foodborne, zoonotic, and waterborne transmission routes. This study aimed to assess the prevalence of HEV in water matrices. Six categories were defined: untreated and treated wastewater, surface water (river, lake, and seawater), drinking water, groundwater, and other water environments (irrigation water, grey water, reservoir water, flood water, and effluent of pig slaughterhouse). We searched PubMed, Web of Science, Global Index Medicus, and Excerpta Medica Database. Study selection and data extraction were performed by at least two independent investigators. Heterogeneity ( I 2 ) was assessed using the χ 2 test on the Cochran Q statistic and H parameter. Sources of heterogeneity were explored by subgroup analysis. This study is registered with PROSPERO, number CRD42021289116. We included 87 prevalence studies from 58 papers, 66.4% of which performed in Europe. The overall prevalence of HEV in water was 9.8% (95% CI 6.4–13.7). The prevalence was higher in untreated wastewater (15.1%) and lower in treated wastewater (3.8%) and in drinking water (4.7%). In surface water, prevalence was 7.4%, and in groundwater, the percentage of positive samples, from only one study available, was 8.3%. Overall, only 36.8% of the studies reported the genotype of HEV, with genotype 3 (HEV-3) prevalent (168 samples), followed by HEV-1 (148 sample), and HEV-4 (2 samples). High-income countries were the most represented with 59/87 studies (67.8%), while only 3/87 (3.5%) of the studies were performed in low-income countries. The overall prevalence obtained of this study was generally higher in industrialized countries. Risk of bias was low in 14.9% of the studies and moderate in 85.1%. The results of this review showed the occurrence of HEV in different waters environments also in industrialized countries with sanitation and safe water supplies. While HEV transmission to humans through water has been widely demonstrated in developing countries, it is an issue still pending in industrialized countries. Better knowledge on the source of pollution, occurrence, survival in water, and removal by water treatment is needed to unravel this transmission path. Graphical Abstract

The search for blue transitions in aquaculture‐dominant countries - Richard S. Cottrell; Danielle M. Ferraro; Gordon D. Blasco; Benjamin S. Halpern; Halley E. Froehlich (Fish and Fisheries, 2021)
The capacity for aquaculture to provide an alternative source of fish and seafood to capture fisheries was once promoted as a tool to reduce demand for wild fish and thus tackle overfishing. To date, there is little evidence to suggest that aquaculture growth has successfully reduced fishing effort on wild populations. Recent theory on “blue transitions” suggests that displacement may only occur as aquaculture production surpasses that of capture operations. Yet, there has been no systematic attempt to understand whether aquaculture‐driven fisheries displacement has occurred in countries where aquaculture is now the dominant production form. We investigate the role of aquaculture on fisheries landings in these “aquaculture‐dominant” countries using national‐level production, trade, consumption and socioeconomic data from 1980 to 2017. Importantly, we find that aquaculture growth is associated with fisheries decline in aquaculture‐dominant countries, but the marginal effects of aquaculture have a far weaker influence on wild‐caught landings than other promoting factors, such as fish consumption and trade. Further, our qualitative analysis of the state of wild fisheries in aquaculture‐dominant nations suggests that overexploitation continues to be pervasive and that any minimal displacement effects from aquaculture are unlikely to have offset the environmental impacts imposed by the growing sector. The rise of aquaculture as an alternative production form can provide valuable insights for growing industries developing sustainable new foods. Unless coupled with effective food consumption policy, such products may simply add to rather than displace the environmental impacts of human food production.

The long and narrow path for novel cell‐based seafood to reduce fishing pressure for marine ecosystem recovery - Benjamin S. Halpern; Jason Maier; Heather J. Lahr; Gordon Blasco; Christopher Costello; Richard S. Cottrell; Olivier Deschenes; Danielle M. Ferraro; Halley E. Froehlich; Gavin G. McDonald; Katherine D. Millage; Michael J. Weir (Fish and Fisheries, 2021)
Cell‐based seafood is an emerging novel food, with many start‐up companies aspiring for ocean conservation benefits through expanded market share that displaces wild‐caught seafood. However, the ability for cell‐based seafood to achieve this conservation outcome is often oversimplified and will rely on an extensive, and we find somewhat tenuous, chain of events. Here, we outline the technological, behavioural, market and ecological changes that must occur along this pathway, and conclude that fisheries recoveries and collateral ocean benefits are unlikely to result from cell‐based seafood technology. In particular, we detail nine necessary steps and argue that failure at any one step could hinder or even eliminate cell‐based seafood's conservation effects. We additionally draw comparisons to aquaculture and share broader lessons for other demand‐driven product interventions.

Substantial Gaps in the Current Fisheries Data Landscape - Gordon D. Blasco; Danielle M. Ferraro; Richard S. Cottrell; Benjamin S. Halpern; Halley E. Froehlich (Frontiers in Marine Science, 2020)
Effective management of aquatic resources, wild and farmed, has implications for the livelihoods of dependent communities, food security, and ecosystem health. Good management requires information on the status of harvested species, yet many gaps remain in our understanding of these species and systems, in particular the lack of taxonomic resolution of harvested species. To assess these gaps we compared the occurrence of landed species (freshwater and marine) from the United Nations Food and Agriculture Organization (FAO) global fisheries production database to those in the International Union for Conservation of Nature (IUCN) Red List and the RAM Legacy Stock Assessment Database, some of the largest and most comprehensive global datasets of consumed aquatic species. We also quantified the level of resolution and trends in taxonomic reporting for all landed taxa in the FAO database. Of the 1,695 consumed aquatic species or groups in the FAO database considered in this analysis, a large portion (35%) are missing from both of the other two global datasets, either IUCN or RAM, used to monitor, manage, and protect aquatic resources. Only a small number of all fished taxa reported in FAO data (150 out of 1,695; 9%) have both a stock assessment in RAM and a conservation assessment in IUCN. Furthermore, 40% of wild caught landings are not reported to the species level, limiting our ability to effectively account for the environmental impacts of wild harvest. Landings of invertebrates (44%) and landings in Asia (>75%) accounted for the majority of harvest without species specific information in 2018. Assessing the overlap of species which are both farmed and fished to broadly map possible interactions – which can help or hinder wild populations - we found 296 species, accounting for 12% of total wild landings globally, and 103 countries and territories that have overlap in the species caught in the wild and produced through aquaculture. In all, our work highlights that while fisheries management is improving in many areas there remain key gaps in data resolution that are critical for fisheries assessments and conservation of aquatic systems into the future.

Velocity scales in steady-nonuniform turbulent flows with low relative submergence - D. Ferraro; S. Servidio; R. Gaudio (Environmental Fluid Mechanics, 2019)

In situ and ex situ bioremediation of seleniferous soils from northwestern India - Shrutika L. Wadgaonkar; Alberto Ferraro; Yarlagadda V. Nancharaiah; Karaj S. Dhillon; Massimiliano Fabbricino; Giovanni Esposito; Piet N. L. Lens (Journal of Soils and Sediments, 2019)

Occurrence and Genetic Diversity of Human Cosavirus in Sewage in Italy - G. Bonanno Ferraro; P. Mancini; M. Divizia; E. Suffredini; S. Della Libera; M. Iaconelli; G. La Rosa (Food and Environmental Virology, 2018)

A multidisciplinary approach to study confined marine basins: the holobenthic and merobenthic assemblages in the Mar Piccolo of Taranto (Ionian Sea, Mediterranean) - L. Ferraro; F. Rubino; M. Belmonte; S. Da Prato; M. Greco; F. Frontalini (Marine Biodiversity, 2017)

Glyphosate input modifies microbial community structure in clear and turbid freshwater systems - H. Pizarro; M. S. Vera; A. Vinocur; G. Pérez; M. Ferraro; R. J. Menéndez Helman; M. dos Santos Afonso (Environmental Science and Pollution Research, 2016)

Multi-center evaluation of the VITEK® MS system for mass spectrometric identification of non-Enterobacteriaceae Gram-negative bacilli - R. Manji; M. Bythrow; J. A. Branda; C.-A. D. Burnham; M. J. Ferraro; O. B. Garner; R. Jennemann; M. A. Lewinski; A. B. Mochon; G. W. Procop; S. S. Richter; J. A. Rychert; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Pulmonary Inflammation and Cell Death in Mice After Acute Exposure to Air Particulate Matter From an Industrial Region of Buenos Aires - F. Astort; M. Sittner; S. A. Ferraro; N. S. Orona; G. A. Maglione; A. De la Hoz; D. R. Tasat (Archives of Environmental Contamination and Toxicology, 2013)

Recurrent Varicella following Steroids and Fingolimod in a Multiple Sclerosis Patient - D. Ferraro; S. De Biasi; F. Vitetta; A. M. Simone; L. Federzoni; V. Borghi; A. Cossarizza; P. F. Nichelli; P. Sola (Journal of Neuroimmune Pharmacology, 2013)

Identification of Enterobacteriaceae by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry using the VITEK MS system - S. S. Richter; L. Sercia; J. A. Branda; C.-A. D. Burnham; M. Bythrow; M. J. Ferraro; O. B. Garner; C. C. Ginocchio; R. Jennemann; M. A. Lewinski; R. Manji; A. B. Mochon; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Recorded ground motion and site effects evaluation for the April 6, 2009 L’Aquila earthquake - M. Maugeri; A. L. Simonelli; A. Ferraro; S. Grasso; A. Penna (Bulletin of Earthquake Engineering, 2011)

New evidences of Roundup® (glyphosate formulation) impact on the periphyton community and the water quality of freshwater ecosystems - María S. Vera; Leonardo Lagomarsino; Matías Sylvester; Gonzalo L. Pérez; Patricia Rodríguez; Hernán Mugni; Rodrigo Sinistro; Marcela Ferraro; Carlos Bonetto; Horacio Zagarese; Haydée Pizarro (Ecotoxicology, 2010)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Long term monitoring of oil spills in European seas - G. Ferraro; S. Meyer‐Roux; O. Muellenhoff; M. Pavliha; J. Svetak; D. Tarchi; K. Topouzelis (International Journal of Remote Sensing, 2009)

Purification and properties of Sandercyanin, a blue protein secreted in the mucus of blue forms of walleye, Sander vitreus - Chi-Li Yu; Daniel Ferraro; S. Ramaswamy; Mark H. Schmitz; Wayne F. Schaefer; David T. Gibson (Environmental Biology of Fishes, 2008)

Burkholderia cepacia complex nasal isolation in immunocompetent patients with sinonasal polyposis not associated with cystic fibrosis - G. Marioni; R. Rinaldi; C. Staffieri; G. Ottaviano; R. Marchese-Ragona; L. Giacomelli; S. M. Ferraro; A. Staffieri (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Apoptosome impairment during development results in activation of an autophagy program in cerebral cortex - Sandra Moreno; Valentina Imbroglini; Elisabetta Ferraro; Cinzia Bernardi; Alessandra Romagnoli; Albert S. Berrebi; Francesco Cecconi (Apoptosis, 2006)

Nest Poaching in Neotropical Parrots - Timothy F. Wright; Catherine A. Toft; Ernesto Enkerlin‐Hoeflich; Jaime Gonzalez‐Elizondo; Mariana Albornoz; Adriana Rodríguez‐Ferraro; Franklin Rojas‐Suárez; Virginia Sanz; Ana Trujillo; Steven R. Beissinger; Vicente Berovides A.; Xiomara Gálvez A.; et al. (Conservation Biology, 2001)
Although the poaching of nestlings for the pet trade is thought to contribute to the decline of many species of parrots, its effects have been poorly demonstrated. We calculated rates of mortality due to nest poaching in 23 studies of Neotropical parrots, representing 4024 nesting attempts in 21 species and 14 countries. We also examined how poaching rates vary with geographic region, presence of active protection programs, conservation status and economic value of a species, and passage of the U.S. Wild Bird Conservation Act. The average poaching rate across all studies was 30% of all nests observed. Thirteen studies reported poaching rates of ≥20%, and four reported rates openface> 70%. Only six studies documented no nest poaching. Of these, four were conducted on islands in the Caribbean region, which had significantly lower poaching rates than the mainland Neotropics. The other two studies that showed no poaching were conducted on the two species with the lowest economic value in our sample ( U.S. retail price). In four studies that allowed direct comparison between poaching at sites with active nest protection versus that at unprotected sites, poaching rates were significantly lower at protected sites, suggesting that active protection efforts can be effective in reducing nest poaching. In those studies conducted both before and after the passage of the U.S. Wild Bird Conservation Act, poaching rates were found to be significantly lower following its enactment than in the period before. This result supports the hypothesis that the legal and illegal parrot trades are positively related, rather than inversely related as has been suggested by avicultural interests. Overall, our study indicates that poaching of parrot nestlings for economic gain is a widespread and biologically significant source of nest mortality in Neotropical parrots.

Phototoxic Evaluation of Marine Sediments Collected from a PAH-Contaminated Site - B. L. Boese; R. J. Ozretich; J. O. Lamberson; F. A. Cole; R. C. Swartz; S. P. Ferraro (Archives of Environmental Contamination and Toxicology, 2000)

Solar Activity and Algal-bloom Occurrences in the Northern Adriatic Sea: Geomagnetic Connection - S. Ferraro; A. Mazzarella (Theoretical and Applied Climatology, 1998)

Effects of DDT sediment-contamination on macrofaunal community structure and composition in San Francisco Bay - S. P. Ferraro; F. A. Cole (Marine Biology, 1997)

Distribution of VP7 serotypes and VP4 genotypes among rotavirus strains recovered from Italian children with diarrhea - S. Arista; E. Vizzi; D. Ferraro; A. Cascio; R. Di Stefano (Archives of Virology, 1997)

Verification of a scattering-based algorithm for estimating rainfall over the open ocean - J. S. Greene; M. L. Morrissey; R. R. Ferraro (Theoretical and Applied Climatology, 1997)

Le pollinosi da oleacee. Indagine aerobiologica nell'atmosfera della città di Palermo - I. Cricchio; M. Zambito; A. Ferraro; D. Minutella; S. Corrao; E. Fileccia; G. Passalacqua (Aerobiologia, 1987)